Iron oxide magnetic powder and its manufacturing method
By applying hydrothermal treatment to a slurry containing ε-iron oxide particles, the method significantly reduces the content of fine particles, addressing the challenge of achieving high recording density and improved noise reduction in magnetic recording media.
Patent Information
- Application Number
- JP2020091704
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-05-26
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2040-05-26
AI Technical Summary
The existing methods for producing iron-based oxide magnetic powders with ε-iron oxide particles, where part of the Fe site is replaced with other metal elements, do not sufficiently reduce the content of fine particles, leading to issues with high recording density in magnetic recording media.
The method involves subjecting a slurry containing ε-iron oxide particles to hydrothermal treatment, which reduces the proportion of fine particles with a particle diameter of 8 nm or less, resulting in a magnetic powder with improved coercive force distribution and reduced noise in electromagnetic conversion characteristics.
This approach effectively reduces the content of fine particles in the iron-based oxide magnetic powder, enhancing the recording density and noise reduction capabilities of magnetic recording media.
Smart Images

Figure 0007656287000003 
Figure 0007656287000004 
Figure 0007656287000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an iron-based oxide magnetic powder suitable for high-density magnetic recording media, radio wave absorbers, etc., and in particular to an iron-based oxide magnetic powder having an average particle size on the order of nanometers, and a method for producing the same. [Background technology]
[0002] ε-Fe 2 O 3 is an extremely rare phase among iron oxides, but at room temperature, nanometer-sized particles have a thermal conductivity of 20 kOe (1.59 × 10 6 A / m) and therefore ε-Fe 2 O 3 A manufacturing method for synthesizing the above in a single phase has been investigated (see Patent Document 1). In addition, ε-Fe 2 O 3 At present, there is no material for a magnetic head having a high level of saturation magnetic flux density that can be used for a magnetic recording medium. 2 O 3 The coercive force has also been adjusted by substituting a portion of the Fe sites with trivalent metals such as Al, Ga, and In, and the relationship between the coercive force and the radio wave absorption characteristics has also been investigated (see Patent Document 2).
[0003] ε-Fe 2 O 3 Since it is obtained as a stable phase with a size on the order of nanometers, a special method is required for its production. The above-mentioned Patent Documents 1 and 2 disclose a method for producing ε-Fe oxyhydroxide by using fine crystals of iron oxyhydroxide produced by a liquid phase method as a precursor, coating the precursor with silicon oxide by a sol-gel method, and then subjecting the precursor to heat treatment. 2 O 3 As the liquid phase method, a reverse micelle method using an organic solvent as the reaction medium and a method using only an aqueous solution as the reaction medium are disclosed.
[0004] On the other hand, in the field of magnetic recording, magnetic recording media with a high carrier-to-noise ratio (C / N ratio) is being developed, and there is a demand for finer magnetic particles constituting the magnetic recording layer in order to achieve higher recording density. In addition, there is a demand for reducing the variation in coercive force distribution caused by the presence of fine particles with small coercive force contained in the iron oxide magnetic powder in order to achieve higher magnetic recording density.
[0005] Patent Document 3 describes ε-Fe 2 O 3 ε-Fe in which some of the particles or Fe sites are replaced by other metal elements 2 O 3 The document discloses a method for producing ε-type iron oxide magnetic powder, which comprises adding a quaternary ammonium salt as a surface modifier to a slurry containing particles, adjusting the pH of the slurry to 11 to 14, dispersing the ε iron oxide particles, and then classifying them. The document also describes that the use of the production method makes it possible to obtain ε-type iron oxide magnetic powder having a small particle size and narrow particle size and coercive force distributions. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2008-174405 A [Patent Document 2] International Publication No. 2008 / 029861 [Patent Document 3] JP 2019-175539 A Summary of the Invention [Problem to be solved by the invention]
[0007] The iron-based oxide magnetic powder, which is made of ε-iron oxide particles in which some of the Fe sites are substituted with other metal elements and which is manufactured by the manufacturing method disclosed in Patent Document 3, has a narrow particle size distribution and a low content of fine particles that do not contribute to the magnetic recording characteristics, and as a result, is excellent in that it has a narrow coercive force distribution. However, according to the investigations of the present inventors, there are problems with quality from the viewpoint of increasing the recording density of magnetic recording media.
[0008] This problem will now be described in detail. When applying an iron-based oxide magnetic powder consisting of ε-iron oxide particles to a magnetic recording medium, it is desirable that the proportion of fine particles whose particle diameter is far from the average particle diameter is as small as possible, because the presence of such fine particles, even if their volume ratio in the magnetic powder is small, causes an increase in noise in the electromagnetic conversion characteristics (SNR) of the magnetic recording medium.
[0009] Furthermore, the iron-based oxide magnetic powder made of ε-iron oxide particles in which some of the Fe sites have been substituted with other metal elements, which is produced by the production method disclosed in Patent Document 3, cannot be said to have a sufficiently reduced content of fine particles, and therefore poses a problem from the viewpoint of increasing the recording density of magnetic recording media.
[0010] The present invention has been made under the above circumstances, and the problem to be solved by the present invention is to provide a method for producing an iron-based oxide magnetic powder consisting of ε-iron oxide particles in which the content of fine particles is reduced and part of the Fe sites is substituted with other metal elements, and also to provide an iron-based oxide magnetic powder consisting of ε-iron oxide particles in which the content of fine particles is reduced and part of the Fe sites is substituted with other metal elements. [Means for solving the problem]
[0011] In order to solve the above-mentioned problems, the present inventors conducted intensive research and as a result, obtained the groundbreaking discovery that the content of fine particles can be reduced by subjecting a slurry containing ε-iron oxide particles in which Fe sites including fine particles are partially substituted with other metal elements to a hydrothermal treatment, thereby completing the present invention.
[0012] That is, the first invention for solving the above-mentioned problems is: A method for producing an iron-based oxide magnetic powder consisting of epsilon-iron oxide particles in which a portion of the Fe sites is substituted with another metallic element, the method comprising subjecting a raw material slurry containing epsilon-iron oxide particles in which a portion of the Fe sites is substituted with another metallic element to hydrothermal treatment. The second invention is The first aspect of the present invention provides a method for producing an iron-based oxide magnetic powder, characterized in that the hydrothermal treatment reduces the percentage of particles of ε-iron oxide in which part of the Fe sites are substituted with other metal elements and which have a particle diameter of 8 nm or less as measured by a transmission electron microscope. The third invention is The second aspect of the present invention provides a method for producing an iron-based oxide magnetic powder, characterized in that the proportion of particles having a particle diameter of 8 nm or less as measured by a transmission electron microscope is reduced to 4% or less. The fourth invention is The method for producing an iron-based oxide magnetic powder according to any one of the first to third aspects of the present invention is characterized in that the hydrothermal treatment is carried out at a temperature of 120° C. or higher. The fifth invention is The method for producing an iron-based oxide magnetic powder according to any one of the first to fourth aspects of the present invention is characterized in that the hydrothermal treatment is carried out at a pressure of 0.2 MPa or more. The sixth invention is The method for producing an iron-based oxide magnetic powder according to any one of the first to fifth aspects of the present invention is characterized in that the raw material slurry containing the ε-iron oxide particles has a pH of 6 or more and 14 or less. The seventh invention is The method for producing an iron-based oxide magnetic powder according to any one of the first to sixth aspects of the present invention is characterized in that the raw material slurry containing ε-iron oxide particles is a slurry containing ε-iron oxide particles in which part of the Fe sites have been substituted with other metal elements and whose average particle diameter measured by a transmission electron microscope is 10 nm or more and 20 nm or less. The eighth invention is The method for producing an iron-based oxide magnetic powder according to any one of the first to seventh aspects of the present invention is characterized in that Ga is used as the other metal element substituting a portion of the Fe sites. The ninth invention is This is a method for producing an iron-based oxide magnetic powder according to any one of the first to eighth aspects of the present invention, characterized in that a raw material slurry containing the ε-iron oxide particles is irradiated with ultrasonic waves and / or metal ions are added thereto, and then the raw material slurry is subjected to a hydrothermal treatment. The tenth invention is The iron-based oxide magnetic powder is characterized in that it has an average particle size of 10 nm or more and 20 nm or less as measured by a transmission electron microscope, the number ratio of particles with a particle size of 8 nm or less is 4% or less, and the content of α-type iron-based oxide as measured by X-ray diffraction is 10% or less. The magnetic powder is composed of ε-iron oxide particles in which part of the Fe sites are substituted with other metal elements. The eleventh invention is A tenth aspect of the present invention provides the iron-based oxide magnetic powder, characterized in that the other metal element substituting a portion of the Fe sites is Ga. Effect of the Invention
[0013] The method of the present invention for producing an iron-based oxide magnetic powder made of ε-iron oxide particles in which part of the Fe sites is substituted with other metal elements can provide an iron-based oxide magnetic powder made of ε-iron oxide particles with a reduced content of fine particles. [Brief description of the drawings]
[0014] [Figure 1] 1 is a TEM photograph of the substituted ε iron oxide particles according to Example 1. [Diagram 2] 1 is a TEM photograph of the iron-based oxide magnetic powder according to Example 1. [Diagram 3] 4 is a TEM photograph of the iron-based oxide magnetic powder according to Example 4. [Figure 4] 11 is a TEM photograph of the iron-based oxide magnetic powder according to Example 7. [Diagram 5] 1 is a TEM photograph of the substituted ε iron oxide particles according to Example 10. [Figure 6] 1 is a TEM photograph of the iron-based oxide magnetic powder of Example 10. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The method for producing an iron-based oxide magnetic powder made of ε-iron oxide particles in which Fe sites are partially substituted with other metal elements according to the present invention is characterized in that a slurry containing ε-iron oxide particles in which Fe sites are partially substituted with other metal elements (sometimes referred to as "raw slurry" in the present invention) is subjected to hydrothermal treatment. The hydrothermal treatment is preferably performed at a temperature of 120° C. or higher and at a pressure of 0.2 MPa or higher, and the raw slurry used preferably has a pH of 6 to 14. The raw slurry used preferably has an average particle size of 10 nm to 20 nm measured by a transmission electron microscope and contains ε-iron oxide particles in which Fe sites are partially substituted with other metal elements, and the raw slurry is preferably irradiated with ultrasonic waves before being subjected to hydrothermal treatment. The present invention also relates to an iron-based oxide magnetic powder consisting of particles of ε-iron oxide in which a portion of the Fe sites is substituted with another metal element, characterized in that the average particle size measured by a transmission electron microscope is 10 nm to 20 nm, the number ratio of fine particles having a particle size of 8 nm or less in a given number of particles of substituted ε-iron oxide (in the present invention, the number ratio of fine particles in a given number of particles of substituted ε-iron oxide may be simply referred to as "number ratio") is preferably 4% or less, and the content of α-type iron-based oxide measured by X-ray diffraction method is 10% or less. The metal element substituting a portion of the Fe sites may be Ga.
[0016] Hereinafter, the present invention will be described in detail in the order of [Method for producing iron-based oxide magnetic powder] and [Iron-based oxide magnetic powder]. In this description, "ε-iron oxide in which part of the Fe sites is substituted with other metal elements" will be referred to as "substitutional ε-iron oxide" and "ε-iron oxide particles in which part of the Fe sites is substituted with other metal elements" will be referred to as "substitutional ε-iron oxide particles".
[0017] [Method of manufacturing iron-based oxide magnetic powder] The method for producing the iron-based oxide magnetic powder according to the present invention will be described in detail in the following order: 1. Production of raw material slurry, 2. Pretreatment of the raw material slurry, and 3. Hydrothermal treatment of the raw material slurry.
[0018] 1. Preparation of raw slurry First, a slurry containing substituted ε iron oxide particles is prepared as a raw material slurry. Since the raw material slurry contains the substituted ε iron oxide particles, the substituted ε iron oxide particles according to the present invention can be obtained after a hydrothermal treatment described later.
[0019] The substituted ε-iron oxide particles can be prepared by using a known manufacturing method for iron-based oxide magnetic powder made of ε-iron oxide particles, such as those disclosed in JP2019-175539A and JP2017-024981A.
[0020] A raw material slurry is obtained by mixing the substituted ε iron oxide particles obtained by the above-mentioned known production method with a solvent, where the solvent is preferably water. As described in paragraph (0041) of JP 2017-024981 A regarding the silicon oxide coating removal process, a slurry containing substituted ε-iron oxide particles coated with silicon oxide is immersed in an aqueous solution of strong alkali and stirred to dissolve and remove silicon oxide from the substituted ε-iron oxide particles. Thereafter, utilizing the property that the substituted ε-iron oxide particles cannot pass through an ultrafiltration membrane or the like, whereas the dissolved silicon oxide and unnecessary ions constituting the strong alkali can pass through an ultrafiltration membrane or the like, the slurry containing the substituted ε-iron oxide particles may be washed with water to remove the dissolved silicon oxide and unnecessary ions, thereby obtaining a raw material slurry.
[0021] The composition and particle size of the substituted ε iron oxide particles contained in the raw material slurry are not particularly limited, and may be adjusted according to the composition and particle size of the iron-based oxide magnetic powder to be finally obtained. The concentration of the substituted ε iron oxide particles in the raw material slurry is also not particularly limited, and may usually be about 0.1 to 10 mass %.
[0022] Here, the composition of the substituted ε-iron oxide particles to which the production method of the present invention can be applied will be described. (1) General formula ε-C z Fe 2-z O 3 (wherein C is one or more trivalent metallic elements selected from In, Ga, and Al). (2) General formula ε-A x B y Fe 2-x-y O 3 (wherein A is one or more divalent metal elements selected from Co, Ni, Mn, and Zn, and B is one or more tetravalent metal elements selected from Ti and Sn). (3) General formula ε-A x C z Fe 2-x-z O 3 (wherein A is one or more divalent metal elements selected from Co, Ni, Mn, and Zn, and C is one or more trivalent metal elements selected from In, Ga, and Al). (4) General formula ε-B y C z Fe 2-y-zO 3 (Here, B is one or more tetravalent metal elements selected from Ti and Sn, and C is one or more trivalent metal elements selected from In, Ga, and Al). (5) General formula ε-A x B y C z Fe 2-x-y-z O 3 (Here, A is one or more divalent metal elements selected from Co, Ni, Mn, and Zn, B is one or more tetravalent metal elements selected from Ti and Sn, and C is one or more trivalent metal elements selected from In, Ga, and Al).
[0023] In addition, the substitution amounts x, y, and z in each of the general formulas described in (1) to (5) above can be arbitrary amounts within the ranges of 0 < x < 1, 0 < y < 1, and 0 < z < 1. And by adjusting the substitution amounts x, y, and z, it is possible to adjust the coercive force to a desired value.
[0024] In the iron-based oxide magnetic powder composed of substituted ε-iron oxide particles produced by the method for producing an iron-based oxide magnetic powder according to the present invention, there may be cases where heterogeneous phases, which are impurities inevitably generated during production, are mixed. The heterogeneous phase is mainly an α-type iron-based oxide. And in the iron-based oxide magnetic powder composed of substituted ε-iron oxide particles obtained by the production method according to the present invention, the inclusion of the α-type iron-based oxide is allowed, but it is preferable that its content is suppressed. Incidentally, the α-type iron-based oxide refers to α-Fe 2 O 3 and α-Fe in which part of the Fe sites are substituted with other metal elements 2 O 3 which is a general term for (in the present invention, the α-type iron-based oxide may be described as "α-phase").
[0025] From the viewpoint of suppressing an increase in the content rate of the α-phase in the iron-based oxide magnetic powder obtained after the hydrothermal treatment described later, the raw material slurry preferably has a pH of 6 or more and 14 or less. By making the pH of the raw material slurry 6 or more, the α-phase content of the obtained iron-based oxide magnetic powder can be suppressed. Also, by making the pH of the raw material slurry 14 or less, it is possible to avoid the effect of suppressing the increase in the α-phase content reaching a plateau, and also to avoid an increase in the chemical cost of the alkaline agent, which is preferable.
[0026] If the raw material slurry does not have a desired pH range, the slurry may be used after adjusting the pH to the desired range by adding an acid, an alkali, etc. Examples of the acid to be added include inorganic acids such as sulfuric acid, nitric acid, hydrochloric acid, and acetic acid, and examples of the alkali to be added include inorganic alkalis such as alkali metal hydroxides such as sodium hydroxide, alkaline earth metal hydroxides such as calcium hydroxide, and ammonia.
[0027] In the present invention, the pH value is measured using a glass electrode based on JIS Z8802, and is measured using a pH meter calibrated with an appropriate buffer solution corresponding to the pH range to be measured as a pH standard solution. The pH described in the present invention is a value obtained by directly reading the measurement value indicated by a pH meter compensated by a temperature compensation electrode under reaction temperature conditions.
[0028] 2. Pretreatment of raw material slurry It is also preferable to subject the raw material slurry prepared in "1. Production of raw material slurry" to pretreatment such as ultrasonic irradiation and / or metal ion addition to produce a "pretreated slurry".
[0029] The raw material slurry can be irradiated with ultrasonic waves using a known ultrasonic disperser. By irradiating the raw material slurry with ultrasonic waves and then subjecting it to hydrothermal treatment, the content of fine particles in the resulting iron-based oxide magnetic powder can be further reduced compared to the case where ultrasonic irradiation is not performed.
[0030] Metal ions can be added to the raw material slurry by adding a water-soluble metal salt such as ferric nitrate or gallium nitrate to the raw material slurry. The type of metal element of the water-soluble metal salt to be added and the ratio of each element may be adjusted to match the chemical composition of the substituted ε-iron oxide particles contained in the raw slurry, but the type of metal element and the ratio of each element may be set within the range of the substitution amount in each general formula explained in (1) to (5) of "1. Production of raw slurry" above, without adjusting to the chemical composition of the substituted ε-iron oxide particles contained in the raw slurry. Also, only a water-soluble iron salt such as ferric sulfate may be added without adding a substituting metal element. Here, the amount of metal ion to be added is preferably an amount such that the total concentration of metal ions in the raw slurry is 0.1 mol / kg or less. In addition, Fe is used as the iron ion. 3+ The anion species of the water-soluble metal salt to be added may be anion species contained in inorganic acids, such as sulfate ion, nitrate ion, chloride ion, or acetate ion.
[0031] 3. Hydrothermal treatment of raw slurry Hydrothermal treatment is a process in which the material to be treated is kept in hot water at a temperature of over 100°C and under high pressure. By carrying out the hydrothermal treatment in the production method according to the present invention, it is possible to reduce the number ratio of fine particles of substitutional ε-iron oxide contained in the raw material slurry or the raw material slurry after the pretreatment. Although the reason why the number ratio of the fine particles can be reduced is not clear, the inventors presume the following mechanism.
[0032] When the substitutional epsilon iron oxide particles are exposed to high-temperature and high-pressure hot water, a dissolution and reprecipitation reaction of the substitutional epsilon iron oxide particles occurs. This dissolution and reprecipitation reaction dissolves the fine particles of substitutional epsilon iron oxide in the raw material slurry and reprecipitates around the larger substitutional epsilon iron oxide particles. It is believed that the content of fine particles is reduced by the above mechanism. This dissolution and reprecipitation phenomenon is generally known as Ostwald ripening. Specific aspects of the temperature, pressure, time, etc. of the hydrothermal treatment according to the present invention will be described below.
[0033] In order to obtain the effect of reducing the number ratio of fine particles of substitutional ε-iron oxide, which is the object of the present invention, the temperature of the hydrothermal treatment is preferably 120° C. or higher, and more preferably 170° C. or higher. When using a raw material slurry having a high number ratio of fine particles, such as 20% or more of particles with a particle diameter of 8 nm or less, the temperature of the hydrothermal treatment is preferably 280° C. or higher from the viewpoint of ensuring a sufficient effect of reducing the number ratio of fine particles. On the other hand, from the viewpoint of suppressing the proportion of α phase in the obtained iron-based oxide magnetic powder, the temperature is preferably 450° C. or less, and more preferably 380° C. or less. In order to obtain the effect of reducing the number ratio of fine particles of substitutional ε-iron oxide, which is the object of the present invention, the pressure of the hydrothermal treatment is preferably 0.2 MPa or more, and more preferably 10 MPa or more. On the other hand, the upper limit of the hydrothermal treatment pressure is not particularly limited, but from the viewpoint of equipment costs, the pressure may be 600 MPa or less, and may be 100 MPa or less. The time of the hydrothermal treatment is preferably 1 minute or more in order to obtain the effect of reducing the number ratio of fine particles of substitutional ε-iron oxide, which is the object of the present invention. On the other hand, the upper limit of the hydrothermal treatment time is not particularly limited, but from the viewpoint of production costs, the time may be 600 minutes or less, and may be 100 minutes or less. By the above-mentioned operations, the method of the present invention for producing iron-based oxide magnetic powder consisting of ε-iron oxide particles in which part of the Fe sites is substituted with other metallic elements makes it possible to obtain iron-based oxide magnetic powder consisting of ε-iron oxide particles with a reduced proportion of fine particles, without the need for classification. However, it is preferable to carry out a preliminary classification operation before the hydrothermal treatment, if desired. It is also preferable to repeat the hydrothermal treatment several times, if desired.
[0034] [Iron-based oxide magnetic powder] According to the above-described method for producing an iron-based oxide magnetic powder of the present invention, a slurry containing substituted ε-iron oxide particles with a reduced ratio of fine particles can be obtained by subjecting a raw material slurry or a pretreated raw material slurry to the above-described hydrothermal treatment. The obtained slurry is subjected to solid-liquid separation by a known method to recover the solid content, and then dried to obtain an iron-based oxide magnetic powder with a reduced ratio of fine particles. The aspects of the iron-based oxide magnetic powder obtained by the production method according to the present invention will be described in detail in the following order: 1. TEM particle size, 2. crystal structure, 3. α-phase content, and 4. composition.
[0035] 1.TEM particle size In the later process described below, when producing an iron-based oxide magnetic powder for use in a magnetic recording medium, in order to increase the coercive force of the obtained iron-based oxide magnetic powder to a certain degree and to obtain excellent electromagnetic conversion characteristics of the magnetic recording medium, it is preferable that the substituted ε iron oxide particles constituting the iron-based oxide magnetic powder according to the present invention have an average particle diameter measured by a transmission electron microscope (sometimes referred to as "TEM average particle diameter" in the present invention) of 10 nm or more and 20 nm or less. In the present invention, the particle size refers to the particle size of the smallest unit particle (primary particle) whose outline can be observed under a transmission electron microscope.
[0036] As described above, if the average particle size of the substituted ε iron oxide particles measured by a transmission electron microscope becomes too small, the ratio of fine particles that do not contribute to improving the magnetic properties increases, and the magnetic properties per unit weight of the magnetic powder deteriorate. Therefore, the TEM average particle size is preferably 10 nm or more. On the other hand, by making the TEM average particle size 20 nm or less, and more preferably 18 nm or less, it is possible to improve the electromagnetic conversion characteristics when the iron-based oxide magnetic powder is used in a magnetic recording medium.
[0037] In the iron-based oxide magnetic powder according to the present invention, the percentage of fine particles of substituted ε-iron oxide having a TEM particle diameter of 8 nm or less in a predetermined number of substituted ε-iron oxide particles is preferably 4% or less. This is because fine particles of substituted ε-iron oxide having a TEM particle diameter of 8 nm or less have a low coercive force, and therefore cannot be used for magnetic recording even if they are present in a magnetic recording medium. In addition, these particles may lead to an increase in noise components in the electromagnetic conversion characteristics of the magnetic recording medium. The above-mentioned predetermined number of particles of the substitutional ε iron oxide is 200 or more.
[0038] Therefore, it is preferable that the proportion of fine particles of substituted ε-iron oxide having a TEM particle diameter of 8 nm or less in a given number of particles of substituted ε-iron oxide is as small as possible. In the iron-based oxide magnetic powder according to the present invention, the proportion of fine particles of substituted ε-iron oxide having a TEM particle diameter of 8 nm or less is preferably 4% or less. This is because the amount of noise components in the electromagnetic conversion characteristics when the iron-based oxide magnetic powder is used in a magnetic recording medium can be reduced compared to the case of using a conventional iron-based oxide magnetic powder.
[0039] 2. Crystal structure It can be confirmed by X-ray diffraction (XRD), high energy electron diffraction (HEED) and the like that the iron-based oxide magnetic powder according to the present invention has an ε-iron oxide crystal structure.
[0040] 3. Alpha phase content As described above, the iron-based oxide magnetic powder obtained by the manufacturing method of the present invention may contain α-phase. When the iron-based oxide magnetic powder of the present invention is applied to a magnetic recording medium, it is preferable to reduce the content of heterogeneous phases in the iron-based oxide magnetic powder as much as possible. Specifically, when the content of heterogeneous phases in the iron-based oxide magnetic powder is measured by Rietveld analysis of the X-ray diffraction method, it is preferable that the content of α-phase is 10% or less.
[0041] 4.Composition The composition of the iron-based oxide magnetic powder according to the present invention will be the same as that of the substituted ε-iron oxide prepared as the raw material if no metal ion addition is performed as a pretreatment for the hydrothermal treatment. On the other hand, when metal ions are added as a pretreatment for the hydrothermal treatment, the added metal ions are all incorporated as oxides into the iron-based oxide particles, and the composition of the finally obtained iron-based oxide magnetic powder will be a combination of the substituted ε-iron oxide prepared as a raw material and the added metal ions. EXAMPLES
[0042] The present invention will be specifically described below with reference to examples, although the present invention is not limited to these examples. First, the evaluation method and evaluation device for the substituted ε-iron oxide particles obtained by the production method according to the present invention and the iron-based oxide magnetic powder consisting of the substituted ε-iron oxide particles will be described in the following order: 1. TEM measurement, 2. average particle size and particle size distribution measurement, 3. crystallinity evaluation by X-ray diffraction (XRD), 4. magnetic hysteresis curve (B-H curve) measurement, and 5. chemical composition analysis.
[0043] 1. TEM Observation For the TEM observation, a JEM-1011 manufactured by JEOL Ltd. was used. For the observation of the substituted ε-iron oxide particles, a TEM photograph taken at a magnification of 100,000 times was used (the one after removing the silicon oxide coating was used).
[0044] 2.Measurement of average particle diameter and particle size distribution Digitizing was used to evaluate the TEM average particle size and particle size distribution of the substituted ε iron oxide particles. Mac-View Ver. 4.0 was used as the image processing software. When using this image processing software, the particle size of a particle is calculated as the length of the long side of the rectangle that circumscribes the particle and has the smallest area. 200 particles were measured.
[0045] At this time, the selection criteria for particles to be measured from among those shown in the TEM photograph were as follows: (1) Particles with any part lying outside the field of view of the photograph will not be measured. (2) Particles that have clear contours and exist in isolation are measured. (3) Even if a particle deviates from the average particle shape, it will be measured if it is independent and can be measured as a single particle. (4) When particles overlap each other but the boundaries between them are clear and the overall shape of the particle can be determined, each particle is measured as a single particle. (5) Particles that overlap each other, have unclear boundaries, and whose overall shape cannot be determined are not measured as their shape cannot be determined. The number average value of the particle diameters of the particles selected based on the above criteria (1) to (5) was calculated, and this was taken as the average particle diameter of the iron oxide magnetic powder as observed by TEM. In addition, the "standard deviation of the particle diameters of the selected particles" was divided by the "number average value of the particle diameters of the selected particles (=average particle diameter)" to calculate the coefficient of variation of the particle diameters of the iron oxide magnetic powder as observed by TEM. In addition, the number ratio of the selected particles with a particle diameter of 8 nm or less to the number of selected particles was calculated as a percentage to obtain the particle ratio of 8 nm or less, and the number ratio of the selected particles with a particle diameter of 20 nm or more was calculated as a percentage to obtain the particle ratio of 20 nm or more.
[0046] 3. Crystallinity evaluation by X-ray diffraction (XRD) The obtained sample was subjected to powder X-ray diffraction (XRD: Rigaku Corporation, sample horizontal type multipurpose X-ray diffractometer Ultima IV, radiation source CuKα radiation, voltage 40 kV, current 40 mA, 2θ = 10° to 70°). The obtained diffraction pattern was evaluated by Rietveld analysis using integrated powder X-ray analysis software (PDXL2: Rigaku Corporation) based on No. 173025: Iron (III) Oxide-Epsilon and No. 82134: Hematite of ICSD (Inorganic Crystal Structure Database), and the crystal structure and the content of α phase were confirmed.
[0047] 4. Magnetic hysteresis curve (BH curve) measurement The magnetic properties of the obtained iron-based oxide magnetic powder were measured under the following conditions. The magnetic properties were measured using a vibrating sample magnetometer (VSM) (VSM-5 manufactured by Toei Kogyo Co., Ltd.). The applied magnetic field was 1035 kA / m (13 kOe) and the M measurement range was 0.005 A m 2 The magnetic properties were measured with a magnetic field change rate of 15 (kA / m s), a time constant of 0.03 seconds, and a wait time of 0.1 seconds. The attached software (Ver. 2.1) made by Toei Kogyo Co., Ltd. was used for this measurement.
[0048] 5.Chemical composition analysis The chemical composition of the iron-based oxide magnetic powder was analyzed using an Agilent Technologies ICP-720ES, with measurement wavelengths (nm) of Fe: 259.940 nm and Ga: 294.363 nm.
[0049] [Example 1] (Step 1) As a raw material solution, 3000 g of a mixed aqueous solution of ferric nitrate (III) and gallium nitrate was prepared. In this raw material solution, the molar ratio of Fe ions to Ga ions was 1.55:0.45, and the total molar concentration of Fe ions and Ga ions was 0.50 mol / kg. The raw material solution was heated to 40° C. in an air atmosphere, and 275.6 g of a 21.75% aqueous ammonia solution was added all at once while mechanically stirring the solution with a stirring blade, and stirring was continued for 2 hours. Next, 288.8 g of a citric acid solution with a citric acid concentration of 20% by mass was added continuously over 1 hour under the condition of a solution temperature of 40° C., and then 186.1 g of a 21.75% by mass aqueous ammonia solution was added all at once. Thereafter, stirring was maintained for 1 hour under the condition of a solution temperature of 40° C., and a slurry containing crystals of iron oxyhydroxide containing Ga as a substitution element was produced.
[0050] (Step 2) Then, under an atmospheric condition, 833.7 g of tetraethoxysilane (TEOS) was added over 35 minutes while stirring the slurry obtained in step 1 at 40°C. Stirring was then continued for about a day, and a slurry was obtained in which the crystals of iron oxyhydroxide containing the substitution element were coated with the hydrolysis product of TEOS. The obtained slurry was then subjected to solid-liquid separation, and the separated solid was washed and collected as a cake.
[0051] (Step 3) The cake recovered in step 2 was dried to obtain a dry powder, which was then heat-treated at 1,025°C for 4 hours in a furnace in an air atmosphere to obtain a powder consisting of substituted ε-iron oxide particles coated with silicon oxide.
[0052] (Step 4) The powder consisting of the substituted ε iron oxide particles coated with silicon oxide obtained in step 3 was added to a 20 mass % NaOH aqueous solution and stirred at about 60° C. for 24 hours to remove the silicon oxide from the surfaces of the substituted ε iron oxide particles, thereby obtaining a slurry containing the substituted ε iron oxide particles.
[0053] (Step 5) The slurry obtained in step 4 was washed with pure water using an ultrafiltration membrane until the electrical conductivity of the filtrate became ≦10 mS / m, thereby obtaining a raw material slurry containing substituted ε-iron oxide particles. The raw material slurry obtained at this time contained 1 mass % of substituted ε-iron oxide particles. The pH of the obtained raw material slurry was 9.
[0054] The raw slurry obtained in step 5 above was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured. The TEM average particle size was 11.3 nm, the number ratio of particles with a particle size of 8 nm or less was 23.0%, and the coefficient of variation (CV value) was 36%. TEM observation of the raw slurry refers to dropping the raw slurry onto a collodion film on a grid, allowing it to adhere, allowing it to dry naturally, and then subjecting it to TEM observation by carbon deposition. Figure 1 shows a TEM photograph of the substituted ε iron oxide particles contained in the slurry. The length indicated by the white horizontal line shown in the lower right corner of the TEM photograph is 100 nm (the same applies to the following TEM photographs).
[0055] A 1% by mass aqueous sulfuric acid solution was added to the raw material slurry obtained in step 5 to adjust the pH to 6.5 to aggregate the substituted ε iron oxide particles, and then the solid matter was collected by filtration through a membrane filter (pore size 0.2 μm). The collected solid matter was dried to obtain an iron-based oxide magnetic powder consisting of substituted ε iron oxide particles. When the composition of Fe and Ga was analyzed for the obtained iron-based oxide magnetic powder, the molar ratio was Fe:Ga=1.57:0.43. In addition, an XRD measurement was performed on the obtained iron-based oxide magnetic powder, and the α-phase content was found to be 0%.
[0056] (Step 6) 4.7 mL of the raw slurry obtained in step 5 was placed in a 5 mL sealed container and subjected to hydrothermal treatment under conditions of a treatment temperature of 150°C, a treatment time of 5 minutes, and a pressure of 30 MPa, thereby obtaining a slurry containing the substituted ε iron oxide particles of Example 1. The conditions for the treatment of the raw slurry and the hydrothermal treatment described above are shown in Table 1.
[0057] (Step 7) The slurry obtained in step 6 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured, revealing that the TEM average particle size was 11.4 nm, the number ratio of particles with a particle size of 8 nm or less was 17.4%, and the coefficient of variation (CV value) was 33%. Figure 2 shows a TEM photograph of the substituted ε iron oxide particles according to Example 1. Next, 1% by mass of sulfuric acid aqueous solution was added to the slurry obtained in step 6 to adjust the pH to 6.5, and then the slurry was filtered through a membrane filter (pore size 0.2 μm). The solid matter was recovered and then dried to obtain the iron-based oxide magnetic powder of Example 1. The obtained iron-based oxide magnetic powder was subjected to XRD measurement, and the content of the α phase was found to be 0%. The magnetic properties of the obtained iron-based oxide magnetic powder were measured, and the results are shown in Table 1 together with the measurement results of the α-phase content and the chemical composition. The chemical composition of the iron-based oxide magnetic powder was the same as that of the substituted ε iron oxide particles contained in the raw material slurry of Example 1. (The same applies to the following Examples 2 to 10.) The measurement results of the substituted ε iron oxide particles and the iron-based oxide magnetic powder explained above are shown in Table 2.
[0058] [Example 2] A slurry containing the substituted ε iron oxide particles according to Example 2 and an iron-based oxide magnetic powder made of the substituted ε iron oxide particles according to Example 2 were obtained by the same procedure as in Example 1, except that in Step 6 of Example 1, 4.4 mL of the slurry containing the substituted ε iron oxide particles obtained in Step 5 of Example 1 was used as the raw material slurry and hydrothermal treatment was performed under the condition of a treatment temperature of 200° C. As explained in step 7 of Example 1, the obtained slurry containing the substituted ε iron oxide particles according to Example 2 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured, revealing that the TEM average particle size was 12.7 nm, the number ratio of particles with a particle size of 8 nm or less was 12.0%, and the coefficient of variation (CV value) was 32%. Furthermore, the obtained iron-based oxide magnetic powder was subjected to XRD measurement, and the content of the α phase was found to be 0%. The treatment conditions and hydrothermal treatment conditions for the raw material slurry explained above are shown in Table 1. Furthermore, the measurement results for the substituted ε iron oxide particles and the iron-based oxide magnetic powder are shown in Table 2.
[0059] [Example 3] A slurry containing the substituted ε-iron oxide particles according to Example 3 and an iron-based oxide magnetic powder made of the substituted ε-iron oxide particles according to Example 3 were obtained by the same procedure as in Example 1, except that in Step 6 of Example 1, 4.1 mL of the slurry containing the substituted ε-iron oxide particles obtained in Step 5 of Example 1 was used as the raw material slurry and hydrothermal treatment was performed under the condition of a treatment temperature of 250° C. As explained in step 7 of Example 1, the obtained slurry containing the substituted ε iron oxide particles according to Example 3 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured, revealing that the TEM average particle size was 11.9 nm, the number ratio of particles with a particle size of 8 nm or less was 13.8%, and the coefficient of variation (CV value) was 28%. In addition, the obtained iron-based oxide magnetic powder was subjected to XRD measurement, and the content of the α phase was found to be 0%. The treatment conditions and hydrothermal treatment conditions for the raw material slurry explained above are shown in Table 1. Furthermore, the measurement results for the substituted ε iron oxide particles and the iron-based oxide magnetic powder are shown in Table 2.
[0060] [Example 4] The slurry containing the substituted ε-iron oxide particles according to Example 4 and the iron-based oxide magnetic powder composed of the substituted ε-iron oxide particles according to Example 4 were obtained by the same procedure as in Example 1, except that in Step 6 of Example 1, 3.8 mL of the slurry containing the substituted ε-iron oxide particles obtained in Step 5 of Example 1 was used as the raw material slurry and hydrothermal treatment was performed under the condition of a treatment temperature of 300° C. As explained in step 7 of Example 1, the obtained slurry containing the substituted ε iron oxide particles according to Example 4 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured, revealing that the TEM average particle size was 13.1 nm, the number ratio of particles with a particle size of 8 nm or less was 4.2%, and the coefficient of variation (CV value) was 30%. Figure 3 shows a TEM photograph of the iron-based oxide magnetic powder obtained in this example. In addition, the obtained iron-based oxide magnetic powder was subjected to XRD measurement, and the content of the α phase was found to be 3%. The treatment conditions and hydrothermal treatment conditions for the raw material slurry explained above are shown in Table 1. Furthermore, the measurement results for the substituted ε iron oxide particles and the iron-based oxide magnetic powder are shown in Table 2.
[0061] [Example 5] A slurry containing the substituted ε-iron oxide particles according to Example 5 and an iron-based oxide magnetic powder composed of the substituted ε-iron oxide particles according to Example 5 were obtained by the same procedure as in Example 1, except that in Step 6 of Example 1, 3.2 mL of the slurry containing the substituted ε-iron oxide particles obtained in Step 5 of Example 1 was used as the raw material slurry and hydrothermal treatment was performed under the condition of a treatment temperature of 350° C. As explained in step 7 of Example 1, the obtained slurry containing the substituted ε iron oxide particles according to Example 5 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured, revealing that the TEM average particle size was 14.2 nm, the number ratio of particles with a particle size of 8 nm or less was 0.4%, and the coefficient of variation (CV value) was 28%. In addition, the obtained iron-based oxide magnetic powder was subjected to XRD measurement, and the content of the α phase was found to be 5%. The treatment conditions and hydrothermal treatment conditions for the raw material slurry explained above are shown in Table 1. Furthermore, the measurement results for the substituted ε iron oxide particles and the iron-based oxide magnetic powder are shown in Table 2.
[0062] [Example 6] A slurry containing the substituted ε-iron oxide particles according to Example 6 and an iron-based oxide magnetic powder composed of the substituted ε-iron oxide particles according to Example 6 were obtained by the same procedure as in Example 1, except that in Step 6 of Example 1, 3.2 mL of the slurry containing the substituted ε-iron oxide particles obtained in Step 5 of Example 1 was used as the raw material slurry and hydrothermal treatment was performed under conditions of a treatment temperature of 350° C. and a treatment time of 10 minutes. As explained in step 7 of Example 1, the obtained slurry containing the substituted ε iron oxide particles according to Example 6 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured, revealing that the TEM average particle size was 15.4 nm, the number ratio of particles with a particle size of 8 nm or less was 0.4%, and the coefficient of variation (CV value) was 45%. In addition, the obtained iron-based oxide magnetic powder was measured by XRD, and the content of the α phase was found to be 7%. The treatment conditions and hydrothermal treatment conditions for the raw material slurry explained above are shown in Table 1. Furthermore, the measurement results for the substituted ε iron oxide particles and the iron-based oxide magnetic powder are shown in Table 2.
[0063] [Example 7] A slurry containing the substituted ε-iron oxide particles of Example 7 and an iron-based oxide magnetic powder composed of the substituted ε-iron oxide particles of Example 7 were obtained by the same procedure as in Example 1, except that in Step 6 of Example 1, 3.2 mL of the slurry containing the substituted ε-iron oxide particles obtained in Step 5 of Example 1 was used as the raw material slurry and hydrothermal treatment was performed under conditions of a treatment temperature of 350° C. and a treatment time of 30 minutes. As explained in step 7 of Example 1, the obtained slurry containing the substituted ε iron oxide particles according to Example 7 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured, revealing that the TEM average particle size was 15.1 nm, the number ratio of particles with a particle size of 8 nm or less was 0.6%, and the coefficient of variation (CV value) was 36%. Figure 4 shows a TEM photograph of the iron-based oxide magnetic powder obtained in Example 7. Furthermore, the obtained iron-based oxide magnetic powder was subjected to XRD measurement, and the content of the α phase was found to be 8%. The treatment conditions and hydrothermal treatment conditions for the raw material slurry explained above are shown in Table 1. Furthermore, the measurement results for the substituted ε iron oxide particles and the iron-based oxide magnetic powder are shown in Table 2.
[0064] [Example 8] The slurry containing the substituted ε-iron oxide particles of Example 8 and the iron-based oxide magnetic powder consisting of the substituted ε-iron oxide particles of Example 8 were obtained by the same procedure as in Example 1, except that in Step 6 of Example 1, 3.2 mL of the slurry containing the substituted ε-iron oxide particles obtained in Step 5 of Example 1 was used as the raw material slurry and hydrothermal treatment was performed under conditions of a treatment temperature of 350° C. and a treatment time of 60 minutes. As explained in step 7 of Example 1, the obtained slurry containing the substituted ε iron oxide particles according to Example 8 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured, revealing that the TEM average particle size was 15.4 nm, the number ratio of particles with a particle size of 8 nm or less was 0.6%, and the coefficient of variation (CV value) was 36%. In addition, the obtained iron-based oxide magnetic powder was measured by XRD, and the content of the α phase was found to be 12%. The treatment conditions and hydrothermal treatment conditions for the raw material slurry explained above are shown in Table 1. Furthermore, the measurement results for the substituted ε iron oxide particles and the iron-based oxide magnetic powder are shown in Table 2.
[0065] [Example 9] A slurry containing the substituted ε-iron oxide particles of Example 9 and an iron-based oxide magnetic powder composed of the substituted ε-iron oxide particles of Example 9 were obtained by the same procedure as in Example 1, except that in Step 6 of Example 1, 3.2 mL of the slurry containing the substituted ε-iron oxide particles obtained in Step 5 of Example 1 was used as the raw material slurry and hydrothermal treatment was performed under conditions of a treatment temperature of 400° C. and a treatment time of 5 minutes. As explained in step 7 of Example 1, the obtained slurry containing the substituted ε iron oxide particles according to Example 9 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured, revealing that the TEM average particle size was 16.0 nm, the number ratio of particles with a particle size of 8 nm or less was 0.0%, and the coefficient of variation (CV value) was 36%. In addition, the obtained iron-based oxide magnetic powder was measured by XRD, and the content of the α phase was found to be 14%. The treatment conditions and hydrothermal treatment conditions for the raw material slurry explained above are shown in Table 1. Furthermore, the measurement results for the substituted ε iron oxide particles and the iron-based oxide magnetic powder are shown in Table 2.
[0066] [Comparative Example 1] A slurry containing substituted ε-iron oxide particles according to Comparative Example 1 and an iron-based oxide magnetic powder composed of substituted ε-iron oxide particles according to Comparative Example 1 were obtained by the same procedure as in Example 1, except that in Step 6 of Example 1, the slurry containing substituted ε-iron oxide particles obtained in Step 5 of Example 1 was not subjected to hydrothermal treatment. As explained in step 7 of Example 1, the obtained slurry containing the substituted ε iron oxide particles according to Comparative Example 1 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured, revealing that the TEM average particle size was 11.3 nm, the number ratio of particles with a particle size of 8 nm or less was 23.0%, and the coefficient of variation (CV value) was 36%. Furthermore, the obtained iron-based oxide magnetic powder was subjected to XRD measurement, and the content of the α phase was found to be 0%. The treatment conditions for the raw material slurry explained above are shown in Table 1. The measurement results for the substituted ε iron oxide particles and the iron-based oxide magnetic powder are shown in Table 2.
[0067] [Example 10] (Step 1) As a raw material solution, 6000 g of a mixed aqueous solution of ferric chloride (III) and gallium nitrate was prepared. In the raw material solution, the molar ratio of Fe ions to Ga ions was 1.90:0.10, and the total molar concentration of Fe ions and Ga ions was 0.50 mol / kg. The raw material solution was heated to 40° C. in an air atmosphere, and 546.1 g of a 22.46% aqueous ammonia solution was added all at once while mechanically stirring the solution with a stirring blade, and stirring was continued for 2 hours. Next, 577.5 g of an aqueous citric acid solution with a citric acid concentration of 20% by mass was added continuously over 1 hour under the condition of a solution temperature of 40° C., and then 368.7 g of an aqueous ammonia solution with a citric acid concentration of 22.46% by mass was added all at once. Thereafter, stirring was maintained for 1 hour under the condition of a solution temperature of 40° C., and a slurry containing crystals of iron oxyhydroxide containing Ga as a substitution element was produced.
[0068] (Step 2) Then, in an air atmosphere, 1692.7 g of tetraethoxysilane (TEOS) was added over 35 minutes while stirring the slurry obtained in step 1 at 40°C. Stirring was then continued for about a day, and a slurry was obtained in which the crystals of iron oxyhydroxide containing the substitution element were coated with the hydrolysis product of TEOS. The obtained slurry was then subjected to solid-liquid separation, and the separated solid was washed and collected as a cake.
[0069] (Step 3) The cake recovered in step 2 was dried to obtain a dry powder, which was then heat-treated at 957°C for 4 hours in a furnace in an air atmosphere to obtain a powder consisting of substituted ε-iron oxide particles coated with silicon oxide.
[0070] (Step 4) The powder of the substituted ε iron oxide particles coated with silicon oxide obtained in step 3 was added to a 20 mass % NaOH aqueous solution and stirred at 60°C for 24 hours to remove the silicon oxide from the surfaces of the substituted ε iron oxide particles, thereby obtaining a slurry containing the substituted ε iron oxide particles.
[0071] (Step 5) The slurry obtained in step 4 was centrifuged in a centrifuge, the supernatant was removed, pure water was added to form a slurry, and the procedure of centrifuging again in the centrifuge was repeated until the supernatant of the slurry obtained in step 4 had a conductivity of ≦15 mS / m.
[0072] (Step 6) Next, a 25% by mass aqueous solution of tetramethylammonium hydroxide (hereinafter referred to as TMAOH) was added as a surface modifier to the washed slurry obtained in step 5 to obtain a surface modifier-containing slurry. The amount of the TMAOH aqueous solution added was set to an amount such that the TMAOH concentration in the surface modifier-containing slurry was 0.065 mol / kg.
[0073] (Step 7) 40 g of the surface modifier-containing slurry obtained in step 6 was subjected to ultrasonic dispersion treatment for 1 hour using an ultrasonic cleaner (Yamato 5510, manufactured by Branson (Yamato Scientific) Co., Ltd.), and then preliminary classification was performed before the hydrothermal treatment described below.
[0074] 40 g of the surface modifier-containing slurry after ultrasonic dispersion treatment was centrifuged for 30 minutes at 20,000 rpm using an R20A2 rotor of a centrifuge (Hitachi Koki Co., Ltd., himac CR21GII), and 30 g of the supernatant slurry was collected. The gravitational acceleration during the centrifugation treatment was 48,000 G. On the other hand, 30 g of 0.065 mol / kg TMAOH aqueous solution was added to 10 g of the slurry on the precipitation side, and then ultrasonic dispersion was performed again. Then, centrifugal separation was performed again at 20,000 rpm and 48,000 G for 30 minutes, and 30 g of the supernatant slurry was collected. On the other hand, 30 g of 0.065 mol / kg TMAOH aqueous solution was added again to 10 g of the slurry on the precipitation side. This operation was repeated nine times to collect a total of 300 g of the supernatant slurry. After mixing the collected 300 g of the supernatant slurry, 40 g of the supernatant slurry was separated from it.
[0075] The collected supernatant slurry (40 g) was centrifuged at 20,000 rpm for 60 minutes using a R20A2 rotor in a centrifuge (Hitachi Koki Co., Ltd., himac CR21GII), and 30 g of the supernatant slurry containing fine particles was removed to obtain 10 g of the precipitated slurry. The gravitational acceleration during the centrifugation was 48,000 G. Then, 30 g of 0.065 mol / kg TMAOH aqueous solution was added to 10 g of the precipitated slurry, and ultrasonic dispersion was performed again. Then, centrifugal separation was performed again at 20,000 rpm and 48,000 G for 60 minutes, after which 30 g of the supernatant slurry was removed to obtain 10 g of precipitated slurry. This operation was repeated nine times to obtain 10 g of precipitated slurry.
[0076] 30 g of 0.065 mol / kg TMAOH aqueous solution was added to 10 g of the resulting precipitate side slurry, and then ultrasonic dispersion treatment was performed for 1 hour using an ultrasonic cleaner (Yamato5510, manufactured by Branson (Yamato Scientific) Co., Ltd.). Then, 40 g of the precipitate side slurry after ultrasonic dispersion treatment was centrifuged for 45 minutes at a rotation speed of 20,000 rpm using an R20A2 rotor of a centrifuge (himac CR21GII, manufactured by Hitachi Koki Co., Ltd.), 30 g of the supernatant slurry was removed, and 10 g of the precipitate side slurry was obtained. The gravitational acceleration during the centrifugation treatment was 48,000 G. On the other hand, 30 g of 0.065 mol / kg TMAOH aqueous solution was added to 10 g of the precipitated slurry, and ultrasonic dispersion was performed again. Then, the mixture was centrifuged again at 20,000 rpm and 48,000 G for 45 minutes, and 30 g of the supernatant slurry was removed to obtain 10 g of precipitated slurry. This operation was repeated nine times to obtain 10 g of precipitated slurry.
[0077] 30 g of pure water was added to 10 g of the obtained precipitate slurry, and the mixture was subjected to ultrasonic dispersion treatment for 1 hour using an ultrasonic cleaner (Yamato 5510, manufactured by Branson (Yamato Scientific) Co., Ltd.), after which a 1% by mass aqueous sulfuric acid solution was added to adjust the pH to 6.5. The precipitate slurry after pH adjustment was centrifuged in a centrifuge, the supernatant was removed, pure water was added to make a slurry, and the slurry was centrifuged again using a centrifuge. This operation was repeated until the supernatant of the slurry had a conductivity of ≦1 mS / m. Pure water and 20% by mass NaOH were then added to the slurry to adjust the pH to 10, and a slurry containing substituted ε iron oxide particles was obtained.
[0078] (Step 8) A 1% by mass aqueous sulfuric acid solution was added to the slurry containing the substituted ε iron oxide particles obtained in step 7 to adjust the pH to 6.5, and the substituted ε iron oxide particles were coagulated and then filtered through a membrane filter (pore size 0.2 μm) to recover the solid content. The recovered solid content was dried to obtain an iron-based oxide magnetic powder. The composition of Fe and Ga was analyzed for the obtained iron-based oxide magnetic powder, and the molar ratio was Fe:Ga=1.92:0.08. In addition, an XRD measurement was performed on the obtained iron-based oxide magnetic powder, and the α-phase content was found to be 0%. On the other hand, the slurry containing the substituted ε iron oxide particles obtained in step 7 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured. The TEM average particle size was 10.9 nm, the number ratio of particles with a particle size of 8 nm or less was 7.8%, and the coefficient of variation (CV value) was 19%.
[0079] (Step 9) Pure water and a 4 mass % NaOH aqueous solution were added to the slurry containing the substituted ε iron oxide particles obtained in step 7, and the content of the substituted ε iron oxide particles was adjusted to 2 mass % and the pH to 12. Then, 4.5 mL of the adjusted slurry was placed in a 5 mL sealed container and subjected to hydrothermal treatment at a treatment temperature of 200° C. for a treatment time of 5 minutes at a pressure of 40 MPa, thereby obtaining a slurry of substituted ε iron oxide particles according to Example 10. The conditions for the treatment of the raw slurry and the hydrothermal treatment described above are shown in Table 1.
[0080] (Step 10) The slurry obtained in step 9 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured, revealing that the TEM average particle size was 11.0 nm, the number ratio of particles with a particle size of 8 nm or less was 3.9%, and the coefficient of variation (CV value) was 19%. Figure 5 shows a TEM photograph of the substituted ε iron oxide particles of Example 10. The obtained slurry of the substituted ε iron oxide particles according to Example 10 was dried to obtain the iron-based oxide magnetic powder according to Example 10. A TEM photograph of the iron-based oxide magnetic powder particles according to Example 10 is shown in FIG. The iron-based oxide magnetic powder thus obtained was subjected to XRD measurement, and the α-phase content was found to be 0%. The results of measuring the magnetic properties of the iron-based oxide magnetic powder thus obtained, as well as the α-phase content and chemical composition, are shown in Table 2. The measurement results of the substituted ε iron oxide particles and the iron-based oxide magnetic powder explained above are shown in Table 2.
[0081] [Example 11] In step 9 of Example 10, pure water, a 4 mass% NaOH aqueous solution, and ferric nitrate were added to the slurry containing the substituted ε iron oxide particles obtained in step 7 of Example 10, so that the content of the substituted ε iron oxide particles was 2 mass%, the pH was 12, and the Fe(III) ion concentration was 0.056 mol / kg. A slurry containing the substituted ε iron oxide particles of Example 11 and an iron-based oxide magnetic powder consisting of the substituted ε iron oxide particles of Example 11 were obtained by the same procedure as in Example 10, except that 2.2 mL of the adjusted slurry was used for a hydrothermal treatment for a treatment time of 10 minutes. As explained in step 10 of Example 10, the obtained slurry containing the substituted ε iron oxide particles according to Example 11 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured, revealing that the TEM average particle size was 11.8 nm, the number ratio of particles with a particle size of 8 nm or less was 1.3%, and the coefficient of variation (CV value) was 15%. In addition, the obtained iron-based oxide magnetic powder was subjected to XRD measurement, and the content of the α phase was found to be 0%. The treatment conditions and hydrothermal treatment conditions for the raw material slurry explained above are shown in Table 1. The measurement results of the substituted ε iron oxide particles and the iron-based oxide magnetic powder are shown in Table 2. The chemical composition was calculated assuming that the substituted ε iron oxide particles contained in the slurry obtained in step 7 of Example 10 and the iron contained in the iron nitrate added to the slurry were all recovered as solid contents (the same applies to Example 12 below).
[0082] [Example 12] In step 9 of Example 10, pure water, a 4 mass% NaOH aqueous solution, and ferric nitrate were added to the slurry containing the substituted epsilon iron oxide particles obtained in step 7 of Example 10 to adjust the content of the substituted epsilon iron oxide particles to 2 mass%, the pH to 12, and the Fe(III) ion concentration to 0.056 mol / kg. Then, ultrasonic waves were irradiated for 120 minutes using an ultrasonic homogenizer (device name: Yamato 4500, manufactured by Branson (Yamato Scientific) Co., Ltd.), and then hydrothermal treatment was performed for 10 minutes using 2.2 mL of the obtained slurry. In the same manner as in Example 10, a slurry containing the substituted epsilon iron oxide particles of Example 12 and an iron-based oxide magnetic powder consisting of the substituted epsilon iron oxide particles of Example 12 were obtained. As explained in step 10 of Example 10, the obtained slurry containing the substituted ε iron oxide particles according to Example 12 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured, revealing that the TEM average particle size was 12.0 nm, the number ratio of particles with a particle size of 8 nm or less was 0.4%, and the coefficient of variation (CV value) was 14%. In addition, the obtained iron-based oxide magnetic powder was subjected to XRD measurement, and the content of the α phase was found to be 0%. The treatment conditions and hydrothermal treatment conditions for the raw material slurry explained above are shown in Table 1. Furthermore, the measurement results for the substituted ε iron oxide particles and the iron-based oxide magnetic powder are shown in Table 2.
[0083] [Comparative Example 2] A slurry containing the substituted ε iron oxide particles according to Comparative Example 2 and an iron-based oxide magnetic powder consisting of the substituted ε iron oxide particles according to Comparative Example 2 were obtained by the same procedure as in Example 10, except that in step 9 of Example 10, the slurry containing the substituted ε iron oxide particles obtained in step 7 of Example 10 was not subjected to hydrothermal treatment. As explained in step 10 of Example 10, the obtained slurry containing the substituted ε iron oxide particles according to Comparative Example 2 was observed by TEM, and the particle sizes of 200 particles contained in the slurry were measured. The TEM average particle size was 10.9 nm, the number ratio of particles having a particle size of 8 nm or less was 7.8%, and the coefficient of variation (CV value) was 19%. Furthermore, the obtained iron-based oxide magnetic powder was subjected to XRD measurement, and the content of the α phase was found to be 0%. The treatment conditions for the raw material slurry explained above are shown in Table 1. The measurement results for the substituted ε iron oxide particles and the iron-based oxide magnetic powder are shown in Table 2.
[0084] [Comparative Example 3] This is an experimental example in which a slurry containing iron hydroxide was used as the raw material slurry instead of a slurry containing substituted ε iron oxide particles. A 4.455 mL solution of an aqueous ferric nitrate solution (Fe(III) ion concentration 0.055 mol / L) adjusted to pH 12 by adding a 4 mass% NaOH aqueous solution was placed in a 5 mL sealed container and subjected to hydrothermal treatment at a treatment temperature of 200°C, a treatment time of 10 minutes, and a pressure of 40 MPa, thereby obtaining a slurry containing iron oxide particles according to Comparative Example 3. The obtained slurry containing the iron oxide particles according to Comparative Example 3 was subjected to solid-liquid separation, washed, and dried to obtain the iron oxide powder according to Comparative Example 3. The result of XRD measurement of the obtained iron oxide powder showed that α-Fe 2 O 3 and the crystal structure of α-FeOOH was confirmed. The hydrothermal treatment conditions explained above are shown in Table 1. Furthermore, the measurement results of the iron hydroxide particles and the iron-based oxide powder are shown in Table 2.
[0085] [Table 1] [Table 2]
Claims
1. When a raw material slurry containing ε-iron oxide particles in which a part of the Fe site is substituted with another metal element is subjected to a hydrothermal treatment, The hydrothermal treatment is carried out at a temperature of 150° C. or more and 450° C. or less, at a pressure of 10 MPa or more and 100 MPa or less, and for a treatment time of 1 minute or more and 100 minutes or less.
2. 2. The method for producing an iron-based oxide magnetic powder according to claim 1, characterized in that the hydrothermal treatment reduces the number of particles of ε-iron oxide in which a portion of the Fe site is substituted with other metal elements and which have a particle diameter of 8 nm or less as measured by a transmission electron microscope.
3. 3. The method for producing an iron-based oxide magnetic powder according to claim 2, wherein the proportion of particles having a particle diameter of 8 nm or less as measured by a transmission electron microscope is reduced to 4% or less.
4. 4. The method for producing an iron-based oxide magnetic powder according to claim 1, wherein a raw material slurry containing ε-iron oxide particles has a pH of 6 or more and 14 or less.
5. The method for producing an iron-based oxide magnetic powder according to any one of claims 1 to 4, characterized in that a slurry containing ε-iron oxide particles, in which a part of the Fe site is substituted with another metal element and whose average particle diameter measured by a transmission electron microscope is 10 nm or more and 20 nm or less, is used as the raw material slurry containing ε-iron oxide particles.
6. 6. The method for producing an iron-based oxide magnetic powder according to claim 1, wherein Ga is used as the other metal element substituting a portion of the Fe site.
7. The method for producing an iron-based oxide magnetic powder according to any one of claims 1 to 6, characterized in that a raw material slurry containing the ε-iron oxide particles is irradiated with ultrasonic waves and / or metal ions are added thereto, and then the raw material slurry is subjected to a hydrothermal treatment.
8. An iron-based oxide magnetic powder comprising particles of ε-iron oxide in which a portion of the Fe sites is substituted with other metal elements, the particles having an average particle size of 11.0 nm or more and 12.0 nm or less as measured by a transmission electron microscope, the number ratio of particles having a particle size of 8 nm or less being 4% or less, and the content of α-type iron-based oxides as measured by an X-ray diffraction method being 10% or less.
9. 9. The iron-based oxide magnetic powder according to claim 8, wherein the other metal element substituting a portion of the Fe sites is Ga.
Citation Information
Patent Citations
METHOD FOR PRODUCING epsilon-Fe2O3 CRYSTAL
JP2008174405A
Magnetic powder, method of producing magnetic powder, and magnetic recording medium
JP2019003713A
Iron-based oxide magnetic powder and method of producing the same
JP2019175539A
Magnetic crystal for radio wave absorbing material and radio wave absorbent
WO2008029861A1